Diagnostics and treatment of spontaneous intracranial hypotension - Schick, Uta; Musahl, Christian; Papke, Karsten (Minimally invasive neurosurgery, 2010)
Intracranial hypotension is a frequently misdiagnosed syndrome which is caused by reduced intracranial cerebrospinal fluid (CSF) pressure due to spontaneous spinal CSF leakage. We present our series of intracranial hypotension regarding especially the required diagnostic imaging and the treatment.
Gesehen am 06.06.2023